Evaluation of Strategic and Information Technology Alignment Using the Strategic Alignment Model (SAM) at Institut Shanti Bhuana - tessa Januarti (Universitas Kristen Immanuel, 2026)
Alignment between organizational strategy and information technology (IT) is a key factor in improving institutional performance, especially in higher education institutions facing rapid digital transformation. This research aims to evaluate the alignment between institutional strategy and IT at Institut Shanti Bhuana using the Strategic Alignment Model (SAM), in order to identify gaps and provide recommendations for improving IT utilization and institutional effectiveness. This study uses a qualitative descriptive approach with data collected through interviews, observations, and document analysis. The evaluation focuses on four main domains in SAM: business strategy, IT strategy, organizational infrastructure and processes, and IT infrastructure and processes. The results show that Institut Shanti Bhuana has implemented various IT initiatives to support academic and administrative activities; however, gaps remain in strategic planning integration, communication between management and IT units, and optimization of IT resources. These gaps may reduce the effectiveness of IT in supporting institutional goals. The study concludes that improving strategic and IT alignment requires strengthening governance, enhancing communication, and developing integrated IT planning. The findings are expected to provide practical guidance for more effective IT implementation in higher education institutions